Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M., Kemmelmeier ,Markus, Gupta ,Vishal K.; and McKelvey, William (Entrepreneurship & Regional Development, 2019)
This research explores the social-cognitive factors which lead both women and men to pursue ventures consistent with their gendered social identity, therefore, reinforcing the gender gap in entrepreneurship. We measured the self-assessments of individuals presented with experimentally manipulated entrepreneurial opportunities that were either consistent or inconsistent with their self-reported gender. A theoretical model derived from Social Role Theory is presented and tested. It posits that a gender match (mismatch) with the entrepreneurial opportunity results in higher (lower) reported self-efficacy, anticipated social resources, and venture desirability and lower (higher) venture risk perceptions. The experimental data are tested in a sequential mediation SEM model. We find evidence that self-efficacy and anticipated social resources mediate the effect of gender congruency on perceived risk and venture desirability. The results provide insight into the insidious barriers that play a role in reproducing a gender gap in entrepreneurial outcomes by ‘nudging’ women into lower-return ventures in less lucrative industries.
Keywords: Entrepreneur; gender; gender gap; gender norms; gender role; opportunity evaluation; sex

The Green Energy Sector - Nodoushani, Omid; Van den Abbeele, Isaline; Stewart, Carol (Competition Forum, 2015)
Thinking "Green" has become a significant economic trend lately. This research paper offers a better understanding of the background facts of the current hype surrounding "Green Energy." First, the problem of global warming is investigated. Europe has taken a lead role in the fight against global warming in order to meet their objective of 20% renewable energy production by 2020. Many possibilities exist to transform raw biomass into bioenergy fuels, which can then be used for specific energy production purposes: electricity production, warming or transport. Biodiesel, bioethanol, biogas and many other fuels can be produced from biomass.
Keywords: Alternative energy; Alternative energy sources; Biomass; Carbon dioxide; Chlorofluorocarbons; Climate change; Energy industry; Environmental impact; Global warming; Greenhouse effect; Greenhouse gases; Nobel prizes; Renewable resources; Studies; Temperature; Trends; dept.mgt

Recycling and Its Effects on the Environment - Nodoushani, Omid; Stewart, Carol; Kaur, Manpreet (Competition Forum, 2016)
Consumers and businesses have an ethical obligation to do their part to reuse or recycle unwanted items. However, while some consumers and businesses do reuse or recycle e-waste, glass, metal, plastic, paper or textiles, more could be done. Even with environmentalists warning of potential chemical hazards these items produce in landfills, an estimated 85 percent of landfills are filled with unwanted waste. The recycling industry along with local government run media campaigns to raise awareness; however, as a result consumers and businesses may be experiencing information overload which may have a negative impact on consumers ' recycling efforts.
Keywords: Communication; Consumers; Consumption; Electronic waste; Electronics; Energy consumption; Environmental impact; Environmental protection; Environmentalists; Greenhouse gases; Information overload; Landfill; Natural resources; Plastics; Raw materials; Recycling; Textiles; dept.mgt

Darwin’s Deadly Legacy? Why Evolution Matters for Management Studies - Yang, Chulguen; Colarelli, Stephen M.; Holston, Kayong (Research Yearbook, 2010)
Keywords: dept.mgt; peer-reviewed

Understanding human nature: From an evolutionary psychological perspective - Yang, C.; Colarelli, S.; Holston, K. (Journal of International Business Disciplines, 2011)
Keywords: dept.mgt; peer-reviewed

The E-Print Industry and Bookseller Market: A Strategic Perspective - Nodoushani, Omid; Yang, Chalie (Competition Forum, 2011)
Keywords: dept.mgt; peer-reviewed

A Comparative Study on Native-Born and Foreign-Born Female Entrepreneurs: A Narrative Approach - Yang, Chulguen Charlie; Goralski, Margaret A. (Business Research Yearbook, Goralski, Margaret A, 2011)
Keywords: dept.mgt; peer-reviewed

The creative use of music in teaching organizational behavior - Yang, Chulguen (Usiness Research Yearbook, XVIII, 2011)
Keywords: dept.mgt; peer-reviewed

A Creative Use of Films to Enhance Emotional Awareness and Cultural Intelligence - Yang, Chulguen Charlie; Nodoushani, Omid (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Kin Altruism, Psychological Contract and Commitment in Immigrant Businesses: Some Theoretical Propositions - Yang, Chulguen Charlie (QRBD, 2014)
Keywords: dept.mgt; peer-reviewed

Mindfulness and Its Pedagogical Application in Business Education - Chulguen (Charlie) Yang; Goralski, Margaret A. (Journal of International Business Disciplines, 2016)
Mindfulness has gained significant attention and momentum in business and popular culture in the US, Europe, and Australia. There is, however, a paucity of literature on how business students make sense of mindfulness and its practices. Based on our experiences of adopting mindfulness and mindfulness meditation in our teachings of management courses, we have explored how business students make sense of mindfulness and meditation. From a phenomenological perspective, we have examined our students' meditation journals, essays, and their own research on the topic of mindfulness. Based on the findings of previous empirical studies on the positive effects of mindfulness practices and our reflections on the pedagogical potential of mindfulness meditation for business education, we have emphasized that the practice of presence through mindfulness tends to enhance the business students' self-awareness and emotional skills. The implications of adopting mindfulness research and brief and deliberate practices into the business curriculum to develop embodied wisdom are also discussed.
Keywords: BUSINESS education; BUSINESS students; MANAGEMENT; MEDITATION; MINDFULNESS; POPULAR culture; UNITED States; dept.mgt; peer-reviewed

Domain specificity of sex differences in competition - Wieland, Alice; Sarin, Rakesh (Journal of Economic Behavior & Organization, 2012)
There has been much recent literature about sex differences in competition, mostly noting that women are innately less competitive than men (Croson and Gneezy, 2009). This article examines the hypothesis that sex differences in propensity to compete are domain specific. We conducted a 2 (sex)×4 (domain) experiment with 434 participants examining competition decisions, familiarity with the domain, and performance. We find no overall sex differences in rates of competition when collapsing across all four domains, but do find sex differences in rates of competition for individual domains. Additionally we examined the importance of winning at competition on self-esteem using the Contingencies of Self-Worth, Competition subscale (Crocker et al., 2003) and find that the subscale fully mediates the effect of sex on the strength of competitive pay preferences.
Keywords: Competition; Decision-making; Gender differences; Risk; Sex differences; dept.mgt

Gender differences in the endowment effect: Women pay less, but won’t accept less - Wieland, Alice; Sundali, James; Kemmelmeier, Markus; Sarin, Rakesh (Judgment and Decision Making, 2014)
We explore different contexts and mechanisms that might promote or alleviate the gender effect in risk aversion. Our main result is that we do not find gender differences in risk aversion when the choice is framed as a willingness-to-accept (WTA) task. When the choice is framed as a willingness-to-pay (WTP) task, men are willing to pay more and thus exhibit lower risk aversion. However, when the choice is framed as a willingness to accept task, women will not accept less than men. These findings imply gender differences in the endowment effect. We also find that the effect size of the gender difference in risk aversion is reduced or eliminated as the context changes from tasks framed as gambles to other domains; and that attitudes toward gambling mediate the gender effect in gambling framed tasks.
Keywords: dept.mgt; endowment effect; gambling attitudes; gender; peer-reviewed; risk attitudes; risk aversion; sex differences

Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Risk aversion for decisions under uncertainty: Are there gender differences? - Sarin, Rakesh; Wieland, Alice (Journal of Behavioral and Experimental Economics, 2016)
It has become well accepted that women are more risk averse than men. For objective probability gambles, typically used in eliciting risk aversion, we find women generally have a lower valuation than men, thus exhibiting greater risk aversion. This paper investigates whether this finding extends to decisions under uncertainty – where probabilities are not given and individuals may assign different probabilities to the same event (e.g. outcomes of award shows or sporting events).We find that for decisions under uncertainty, men and women value the bets similarly, both before and after controlling for participants' subjective probabilities.
Keywords: Decision-making; Gender; Risk aversion; Subjective probability; Uncertainty; dept.mgt; peer-reviewed

Antecedents of corporate entrepreneurship in Iran: the role of strategic orientation and opportunity recognition - Kakapour, Saba; Morgan, Todd; Parsinejad, Salman; Wieland, Alice (Journal of Small Business & Entrepreneurship, 2016)
In a study of 130 Iranian small- and medium-sized enterprises (SMEs), we predict and find that market orientation, learning orientation, and their interaction are positively related to opportunity recognition, which impacts firm-level corporate entrepreneurship positively. This study makes two important contributions to the corporate entrepreneurship literature. First, the majority of studies on corporate entrepreneurship concern western economies or China; as such, we broaden research on the international context of corporate entrepreneurship by examining a unique dataset of Iranian SMEs, which have grown significantly in recent years during their transition to knowledge-based enterprises. Second, we build upon previous literature on corporate entrepreneurship antecedents by explicating and testing the relationships of how and when learning orientation and market orientation affect opportunity recognition and the development of corporate entrepreneurship.
Keywords: Apprentissage organisationnel; Entreprenariat d'entreprise; Entreprises fondées sur les connaissances; Iran; Orientation de marché; Orientation sur l'apprentissage; Petites et Moyennes Entreprises; Repérage des débouchés; corporate entrepreneurship; dept.mgt; knowledge-based enterprises; learning orientation; market orientation; opportunity recognition; organizational learning; peer-reviewed; small and medium-sized enterprises

Designing Entrepreneurship Experiments: A Review, Typology, and Research Agenda - Hsu, Dan K.; Simmons, Sharon A.; Wieland, Alice M. (Organizational Research Methods, 2017)
This article discusses the current and potential application of experimental methods to the study of entrepreneurship phenomena. Drawing on a review of experimental studies in entrepreneurship research, we discuss the advantages and disadvantages of experimental research designs for entrepreneurship research as a primer for those interested but not overly familiar with these methods. To advance research agendas and theory in the field, we introduce a typology of experimental manipulations that highlight alternative design choices based on the nature of their participant impact and realism of context. Finally, we provide an overview of areas of opportunity within the entrepreneurship literature for application of methods best suited to provide greater insight into the causal mechanisms at play.
Keywords: dept.mgt; peer-reviewed

Culture, benevolent and hostile sexism, and entrepreneurial intentions - Stedham, Yvonne; Wieland, Alice (International Journal of Entrepreneurial Behavior & Research, 2017)
Purpose In this study, the authors relate cultural masculinity to individual level sexist beliefs (hostile and benevolent sexism) and gendered entrepreneurial stereotypes. The purpose of this paper is to explore whether hostile and benevolent sexism affect entrepreneurial intentions and whether this relationship is mediated by gendered entrepreneurial stereotypes. Design/methodology/approach The proposed relationships are explored using a sample of 192 participants from the USA and India with varying interest in starting a business. An online survey instrument was used to collect the data. Regression and mediation analyses were used to analyze the data. Findings The authors find that both hostile and benevolent sexism are positively related to entrepreneurial intentions of both men and women. However, only benevolent sexism is related to both the masculine and feminine gender traits ascribed to entrepreneurs. Interestingly, the authors find support that hostile sexism is actually positively related to feminine traits ascribed to entrepreneurs, albeit with a small effect size. The authors do not find any support that these results vary by participant gender; the findings are implicated for both men and women alike. The authors find that for both hostile and benevolent sexism only the feminine traits perceived as stereotypic of entrepreneurs partly mediate their relationship on entrepreneurial intentions. Research limitations/implications The survey consists of cross-sectional, self-report data, and therefore the authors cannot conclusively infer causality. The direction of relationships found is of theoretical value. Only two countries are included in the sample limiting generalizability to other countries. Most of the participants in the sample reported some interest or experience in nascent entrepreneurial activities, which may limit the generalizability of findings to those without any prior interest or experience as a nascent entrepreneur. Originality/value The relationship between ambivalent sexism (both hostile and benevolent sexism) and both entrepreneurial intentions, and the gendered traits ascribed to entrepreneurs, has not yet been explored before this work. Using the lens of cultural masculinity, we present a theoretical model of how hostile and benevolent sexist attitudes facilitate or inhibit entrepreneurship via how entrepreneurs are perceived. This is the first study we know of which explores the relationship between Ambivalent Sexism and the gender attributes ascribed to entrepreneurs, and how these gendered entrepreneurial stereotypes in turn are related to entrepreneurial intentions.
Keywords: Ambivalent Sexism Scale; Benevolent sexism; Culture; Entrepreneurial intentions; Hostile sexism; Masculinity; Social construction of gender; dept.mgt; peer-reviewed

A Chinese–Canadian Cross-Cultural Investigation of Transformational Leadership, Autonomous Motivation, and Collectivistic Value - Wang, Zheni; Gagné, Marylène (Journal of Leadership & Organizational Studies, 2013)
Synthesizing theories of transformational leadership and self-determination, this research investigated whether transformational leaders (a) promote the autonomous motivation of their subordinates and whether (b) it results in higher autonomous motivation when subordinates hold high collectivistic values. Multilevel data were obtained from work samples in China and Canada. The results showed a positive relation between managers’ transformational leadership and subordinates’ autonomous motivation cross-culturally. Although higher collectivistic values were related to higher autonomous motivation, collectivist values did not significantly moderate the motivational effect of transformational leadership.
Keywords: dept.mgt; peer-reviewed

The Multidimensional Work Motivation Scale: Validation evidence in seven languages and nine countries - Gagné, Marylène; Forest, Jacques; Vansteenkiste, Maarten; Crevier-Braud, Laurence; van den Broeck, Anja; Aspeli, Ann Kristin; Bellerose, Jenny; Benabou, Charles; Chemolli, Emanuela; Güntert, Stefan Tomas; Halvari, Hallgeir; Indiyastuti, Devani Laksmi; et al. (European Journal of Work and Organizational Psychology, 2015)
Self-determination theory proposes a multidimensional conceptualization of motivation comprising autonomous and controlled forms. Whereas autonomous motivation relates positively to individuals’ optimal functioning (e.g., well-being, performance), controlled motivation is less beneficial. To be able to use self-determination theory in the field of organizational behaviour, the Multidimensional Work Motivation Scale was developed and tested using data from 3435 workers in seven languages and nine countries. Factorial analyses indicated that the 19-item scale has the same factor structure across the seven languages. Convergent and discriminant validity tests across the countries also indicate that the psychological needs for autonomy, competence, and relatedness as well as the theoretically derived antecedents to work motivation (e.g., leadership and job design) are predictably related to the different forms of motivation, which in turn are predictably related to important work outcomes (e.g., well-being, commitment, performance, and turnover intentions). Implications for the development of organizational research based on self-determination theory are discussed.
Keywords: Autonomous motivation; Controlled motivation; Cross-cultural; Extrinsic motivation; Intrinsic motivation; Self-determination theory; Validation; Work motivation; dept.mgt

Servant leadership and employee outcomes: the moderating role of subordinates’ motives - Donia, Magda B.L.; Raja, Usman; Panaccio, Alexandra; Wang, Zheni (European Journal of Work and Organizational Psychology, 2016)
Drawing from implicit leadership theories we advance servant leadership theory by examining moderating mechanisms that explain under what conditions servant leader behaviours impact followers in organizations. Specifically, we focused on the moderating role of subordinates’ motivational orientations—prosocial values or impression management motives—in relationships between servant leadership behaviours and job satisfaction, as well as subordinate organizational citizenship behaviours (OCBs). Using time-lagged data collected from 192 supervisor-subordinate dyads, we found that servant leadership was positively associated with employees’ job satisfaction, but not significantly related to their performance of OCBs. We also found evidence that subordinates’ motives moderate the relationships between servant leadership and outcomes. Specifically, employees high on impression management experienced lower levels of job satisfaction than their lower scoring counterparts. Our findings suggest that servant leadership may not be equally beneficial for all followers. We discuss implications for theory and practice.
Keywords: citizenship behaviours; dept.mgt; employee motives; implicit leadership theories; job satisfaction; peer-reviewed; servant leadership

Genetically engineered food and genetically modified organisms - Nodoushani, Omid; Sintay, Jayme; Stewart, Carol (Competition Forum, 2015)
Keywords: dept.mgt; peer-reviewed

Organizations' investment in education - Nodoushani, Omid; Stewart, Carol; Escobar, Jessica (Competition Forum, 2016)
Keywords: dept.mgt; peer-reviewed

Cultivating Employees Using Maslow's Hierarchy of Needs - Stewart, Carol; Nodoushani, Omid; Stumpf, Jason (Competition Forum, 2018)
Stress caused by climates of fear in the workplace is sapping employee decision-making and causing conflict in the workplace. While hard to quantify, it is easy to understand why intelligent and engaged employees are the ideal: there are fewer mistakes and higher productivity. The primary metric used to frame the reasons for motivation is Maslow's Hierarchy of Needs. It is also vitally important to understand the power balance between employees and employers. By the very nature of employment, employers have less need for a particular employee unlike the employee who cannot afford to be unemployed.
Keywords: Business And Economics; Compensation; Competition; Corporate culture; Emotions; Employees; Employers; Employment; Employment security; Empowerment; Games; Handbooks; Happiness; Job satisfaction; Personal computers; Physiology; Software; Stress; Success; Work environment; Workers; dept.mgt; peer-reviewed

Sustainability and Embodiment: How Can You Be in Two Places at Once When You’re No Place at All? - Robbins, Gregory (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Sustainability initiatives: a competing values framework - Robbins, Gregory E.; Page, Mary A. (Competition Forum, 2012)
Keywords: dept.mgt; peer-reviewed

Hidden tradeoffs in sustainability initiatives - Page, Robert A; Robbins, Gregory (International Journal of Interdisciplinary Research, 2013)
Keywords: dept.mgt; peer-reviewed

Knowledge management and organizational performance in the service industry: The role of transformational leadership beyond the effects of transactional leadership - Birasnav, M. (Journal of Business Research, 2014)
This study examines a comprehensive model comprising of various relationships between transformational and transactional leadership, knowledge management (KM) process, and organizational performance. Data are collected from human resource managers and general managers working in 119 service firms. Exploratory factor analysis and hierarchical regression analysis are used to analyze the proposed hypotheses. The results indicate that transformational leadership has strong and positive effects on KM process and organizational performance after controlling for the effects of transactional leadership. Further, KM process partially mediates the relationship between transformational leadership and organizational performance after controlling for the effects of transactional leadership. Implications and directions for future research are also discussed.
Keywords: Knowledge management; Organizational performance; Transactional leadership; Transformational leadership; dept.mgt

Linking Leadership Behaviors and Information Exchange to Improve Supply Chain Performance: A Conceptual Model - Birasnav, M.; Mittal, Rakesh; Loughlin, Selene (Global Journal of Flexible Systems Management, 2015)
Organizations striving to improve cycle time concentrate on developing long-term relationship with suppliers. In order to support organizational efforts, this study develops a conceptual model that explores the relationships among leadership behaviors, relational commitment and trust, information exchange, and cycle time. Although the supply chain management literature mentions leadership behavior in the context of supply chain, there are no studies that examine the impact of leadership behaviors on cycle time. This study proposes that transformational and transactional leadership behaviors of buyers increase the flow of information to suppliers directly as well as indirectly through relational commitment and trust, and these relationships also influence cycle time. However, it also proposes that the impact of transformational leadership behaviors on relational commitment and trust and information exchange is stronger than the impact of transactional leadership behaviors. Additionally, both uncertain environment and supplier base have potential to play moderation roles in the relationship between transformational leadership and relational commitment and trust and between transformational leadership and information exchange.
Keywords: Cycle time; Information exchange; Relational commitment; Relational trust; Supplier base; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Mixed signals: do college graduates have the soft skills that employers want? - Stewart, Carol; Wall, Alison; Marciniec, Sheryl (Competition forum, 2016)
Keywords: dept.mgt; peer-reviewed

Bankruptcy Law and Practice - J.D, Grace A. Luppino; J.D, Robert A. Smith (Pearson, 2015)
Keywords: dept.mgt

Leadership, Generations and Small Business - Just, Renee (Scholars' Press, 2013)
Keywords: dept.mgt

Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Evaluating the Knowledge of Conversational Agents - Park, Mina; Aiken, Milam; Vanjani, Mahesh (Southwestern Business Administration Journal, 2019)
Keywords: dept.bis; dept.mgt; peer-reviewed

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Gender Characterizations in Entrepreneurship: A Multi‐Level Investigation of Sex‐Role Stereotypes about High‐Growth, Commercial, and Social Entrepreneurs* - Gupta, Vishal K.; Wieland, Alice M.; Turban, Daniel B. (Journal of Small Business Management, 2019)
The purpose of this study is to cast new light on possible gender biases in implicit theories people hold about various forms of entrepreneurial activity. Using social role theory, we delve into sex‐role stereotypes associated with high‐ and low‐growth entrepreneurship and commercial and social entrepreneurship. Predictions were tested with an experimental design using both a between‐subject design to capture group‐level stereotypes and a within‐subject design to capture individual‐level stereotypes. Findings reveal that commercial and high‐growth entrepreneurs are perceived as more similar to men than to women and higher on agency than communality. Conversely, low‐growth entrepreneurs are perceived as more similar to women than men, and higher on communality than agency. Social entrepreneurs are uniquely perceived as similar to both men and women, though they are also considered higher on agency than communality. Interestingly, female, but not male respondents, perceive some overlap between the feminine gender role and high‐growth and commercial entrepreneurship. Notably, those higher on modern sexism perceive less overlap between entrepreneurship and femininity. Taken together, our results suggest that commercial high‐growth entrepreneurship is most strongly male‐typed, which is likely to be problematic for women (and non‐traditional men) wanting to start growth‐oriented ventures. Implications and directions for future research are discussed.
Keywords: dept.mgt; peer-reviewed

Exploring the Gender Gap in Tech Companies: Why Aren't There More Women? - Chaudhry, Haroon; Wall, Alison E.; Wall, Jerry L. (Competition Forum, 2019)
Diversity issues in organizations have long been the subject of organizational studies and cultural examinations. While organizations have made several advancements to balance the presence of female representation in their employees, there remains a paucity of women in certain fields, most notably the tech industry where, despite similar performance in courses, women are alarmingly underrepresented. This paper examines this lack of diversity and proposes some remedies for specifically addressing the lack of women in the tech industry and can be extended to participation in any STEM careers that makes up a significant portion of the tech industry.
Keywords: Bullying; Business And Economics; Careers; Employees; Employment; Females; Gender; High tech industries; Litigation; Multiculturalism & pluralism; Research & development--R&D; STEM education; STEM professions; Social networks; Success; Women; dept.mgt; peer-reviewed

Industrial Democracy in The Knowledge Society - Nodoushani, Omid; Robbins, Gregory Gadiel (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

Supply chain integration, advanced manufacturing technology, and strategic leadership: An empirical study - Birasnav, M.; Bienstock, Joshua (Computers & Industrial Engineering, 2019)
Top management support is a crucial investment at any manufacturing firm striving to integrate supply chain partners with the manufacturing processes so as to achieve a competitive advantage. Though the effectiveness of different leadership behaviors exhibited in top-level management has been documented in the leadership literature, the influence of such behaviors on developing linkages with supply chain partners has not been extensively examined. In order to bridge this research gap, this study examines the interlinkages between strategic leadership theory and supply chain integration theory. In addition, it also investigates the interrelationships between these two theories in the context of implementation of advanced manufacturing technology. Data has been collected from 107 small manufacturing companies and was analyzed using structural equation modelling. Results show that transactional leadership exhibited in top-level management is positively related to internal integration within the manufacturing companies. Transformational leadership behavior exhibited in top-level management and advanced manufacturing technology implemented in the shop floor of these companies are positively related to the integration of external supply chain partners. In addition, we also found that in those instances where small manufacturing companies place a high emphasis on the implementation of advanced manufacturing technology, they are guided by transformational leaders who strongly integrate their companies with customers.
Keywords: Advanced manufacturing technology; Customer integration; Internal integration; Small manufacturing industries; Strategic leadership; Supplier integration; dept.mgt; peer-reviewed

Integration of Social Capital and Organizational Learning Theories to Improve Operational Performance - Birasnav, M.; Chaudhary, Richa; Scillitoe, Joanne (Global Journal of Flexible Systems Management, 2019)
This study focuses on integrating the premises of social capital theory and the theory of organizational learning to improve the operational performance of firms nurturing the buyer–supplier relationship. Social capital theory highlights the importance of developing social relationships between firms to create valuable resources and collectively access critical resources. Organizational learning theory highlights that the learning capacity of an organization strongly depends on top-level leaders’ behaviors, organizational structure, culture, and flexibility, and uncertainties in the environment in which the organization functions. Though many studies have focused on the impact of social capital on performance improvements in the buyer–supplier relationship, the interlinkages between social capital and organizational learning have not been given much attention. Based upon these theories, a system-focused perspective, which showcases the antecedents and outcome of the relationship between collaborative communication and learning, has been proposed in this study. A literature review has been carried out to support the linkages in the proposed conceptual model. Findings suggest that transformational buyers support creating cognitive capital with suppliers. This cognitive capital influences the structural capital, which supports improving the understanding of each party’s processes in the buyer–supplier relationship when parties have high long-term orientation. Improved learning capability reshapes organizations into flexible systems capable of responding quickly to customer requirements, and consequently, they realize a higher performance level.
Keywords: Collaborative communication; Information technology competency; Long-term orientation; Organizational learning; Supplier knowledge; Transformational leadership; dept.mgt

Integrating Theories of Strategic Leadership, Social Exchange, and Structural Capital in the Context of Buyer–Supplier Relationship: An Empirical Study - Birasnav, M.; Mittal, Rakesh; Dalpati, Avadhesh (Global Journal of Flexible Systems Management, 2019)
This study is aimed at improving the purchasing cycle time in a buyer–supplier relationship by integrating the facets of strategic leadership, social exchange, and social capital theories. We developed and tested a conceptual model that postulated relationships among strategic leadership behavior, relational trust and commitment, structural capital, and purchasing cycle time. Data were collected from purchase managers and their employees working in 105 manufacturing companies and analyzed using structural equation modeling technique. Our findings indicated that strategic leadership behaviors are positively related to trust in the buyer–supplier relationship. In addition, trust enhances relational commitment between buyer and supplier, which in turn positively relates to information sharing and supplier development. Further, increased information sharing in the relationship results in reduced purchasing cycle time. Implications for both theory and practice are discussed in depth, and directions for future research are suggested.
Keywords: Cycle time; Information sharing; Relational commitment; Relational trust-Strategic leadership; Supplier development; dept.mgt; peer-reviewed

Money and Morality: Leadership in the National Football League - Stewart, Carol; Joyner-McGraw, Laquita (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

Employee Assistance Programs: Balancing Increased Productivity and Engagement Among Employees with Equal Employment and Legal Complience - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition Forum, 2019)
Managing the impact of employees' personal and work-related difficulties on workplace productivity is becoming increasingly salient for organizations. Employee Assistance Programs (EAPs) are one approach to help improve the quality of life for employees and maximize their productivity. While EAPs have many benefits, potential negative ramifications and legal considerations must also be considered. This article highlights some important cases and the best practices for organizations to utilize in creating clear organizational policies that align with equal employment opportunity and privacy laws in collaboration with legal and human resources professionals and employee assistance providers to reduce or eliminate potential liability.
Keywords: Absenteeism; Affirmative action; Business And Economics; Complaints; Confidentiality; Costs; Employees; Employers; Employment discrimination; Human resource management; Labor law; Performance evaluation; Productivity; Sexual harassment; dept.mgt; peer-reviewed; ⛔ No DOI found

Using Action Research to Build a Learning Organization in a New School of Pharmacy. - Hopkins, Pamela (2010)
Keywords: dept.mgt; faculty_collection; sabbatical_report

The Role of Chance in CEO Selection. - Stepanovich, Paul (2010)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Take charge: Understand control charts and know the difference in variation to better manage your people - Stepanovich, P.L.; Hopkins, P.J. (Quality Progress, 2013)
Keywords: dept.mgt; ⛔ No DOI found

Participant carelessness: Is it a substantial problem with survey data? - Marasi, S.; Wall, A.; Brewer, K. (Electronic Journal of Business Research Methods, 2019)
For decades, participant carelessness has been considered a problem in collecting data using surveys. Although participant carelessness cannot be disputed to exist, the impact it has on data quality or the level of influence or bias it produces in results is questionable. The main purpose of this paper is to determine whether participant carelessness is a substantial problem that significantly influences or biases the results of statistical analyses. This is accomplished by analyzing established management relationships through a comparison of the full, careful, and careless samples to determine the impact participant carelessness has on data results regarding correlations, t-tests, and simple linear regressions. Four detection approaches were used to identify careless participants individually, in pairs, and in three method combinations. The second purpose of this paper is to use the resampled individual reliability (RIR) approach to detect careless participants and compare it to the individual reliability approach to determine whether the two approaches are fundamentally similar. Data were collected using Mechanical Turk (N = 678). Based on the findings, participant carelessness does not appear to be a substantial problem or demonstrate levels of bias in the results in this study. There are two significant differences between the full and careful samples with the t-tests and the regression comparisons of fit statistics demonstrate the careful samples to have a weak improvement over the full sample however, none indicate bias. The findings also suggest that the individual reliability and the RIR approaches are not entirely fundamentally similar. © ACPIL.
Keywords: Careless responding; Insufficient effort responding; Participant carelessness; Random responding; dept.mgt; peer-reviewed; ⛔ No DOI found

Chatbots for Multilingual Conversations - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Journal of Management Science and Business Intelligence, 2019)
Chatbots emulate human dialogue to provide a more intuitive user interface to applications or simply provide entertainment. Chatbots rely on technology to function and new and emerging technologies such as NLP (Natural Language Processing) and AI (Artificial Intelligence) can be used to increase the ability of chatbots to emulate a more natural and free flowing conversation. As more and more mobile device users transition to increased use of texts and messaging chatbots can be used to provide consumers with multilingual support and services. While some chatbots have been developed in other languages, currently most converse only in English, and only a few can communicate in multiple languages. If configured correctly multilingual chatbots have the potential of providing a digital communication option that transcends language barriers. For our research we focused on the use of a chatbot that links the English-speaking Tutor Mike system with Google Translate, thus providing conversational capability in 103 languages, which is more than any other artificial multilingual agent is currently capable of. Two humans communicated with the system using German, Spanish, and Korean, and a group of undergraduate students reviewed the English translations of the chatbot’s replies. Results show that the responses from German and Spanish were cogent and natural, but those from Korean were less understandable. As a caveat, Asian languages lack much of the linguistic nuances of European languages. For example, there may be no plural form or gender in the Asian language. Unlike German where nouns and adjectives constantly change endings depending on what they are doing in a sentence and, unlike Spanish, which have numerous verb conjugations, Asian languages require no such changes. This might impact the translation ability and quality of a multilingual chatbot. Additional research and enhancements can improve chatbots used for European to Asian language translations and vice-versa. Regardless, our research shows promising results in the future use of multilingual chatbots to allow communication across the globe with business potential in the use of such chatbots to provide customer service and online live interaction with customers across the world.
Keywords: Chatbot, Multilingual, Communication, Machine Translation; dept.bis; dept.mgt; peer-reviewed

The green MBA: a competing values matrix - Page, Robert A; Collins, Kirsten A (Competitiveness Review: An International Business Journal Incorporating Journal of Global Competitiveness, 2010)
Purpose – The purpose of this paper is to review and categorize the different strategies Master of Business Administration (MBA) programs have adopted towards incorporating environmental sustainability into business administration. Design/methodology/approach – Through extensive internet research looking at colleges and universities, data are collected from primary source web sites and administrative school contacts. There are 35 institutions whose MBA programs address sustainability in some way. Each of these institutions is then organized by location, tuition cost, enrollment, year founded, accreditation, and curriculum. Findings – Green educational strategies differentiate themselves by the size and maturity of the program. Larger, established institutions typically opt for the green major, or a dual degree, and tend to leave systematic integration of sustainability to the individual student. Newer and smaller entrants tend to either dabble in green with a few sustainability courses, or completely embrace and systemically integrate sustainability throughout the program. Research limitations/implications – The sample focuses on US institutions and treats sustainability as an externally validated curricular choice when it may merely be an educational fad. The sample excludes potential green MBA programs that lack a strong internet presence. Practical implications – Four archetypes are identified: dual degree, all-green, green major, and green coursework. Institutions can analyze their performances and see where they fall on the two major continua – integration and maturity/size. Originality/value – Green MBA programs are relatively new on the academic landscape, and this research paper is one of the first to systematically analyze and categorize them. © Emerald Group Publishing Limited.
Keywords: Curricula; Economic sustainability; Education; Environmental studies; Master of business administration; dept.mgt

AACSB accreditation and possible unintended consequences: A deming view. - Stepanovich, Paul L; Mueller, James; Benson, Dan (The Journal of Education for Business, 2014)
The AACSB accreditation process reflects basic quality principles, providing standards and a process for feedback for continuous improvement. However, implementation can lead to unintended negative consequences. The literature shows that while institutionalism and critical theory have been used as a theoretical base for evaluating accreditation, W. E. Deming's philosophy has not. This article fills that void by examining possible negative consequences in meeting faculty qualification requirements in institutions with a teaching mission. © 2014, Copyright Taylor & Francis Group, LLC.
Keywords: AACSB accreditation; Deming; dept.mgt; profound knowledge

Time horizon of investments in the resource allocation process: review and framework for next steps - Reilly, Greg; Souder, David; Ranucci, Rebecca (Journal of Management, 2016)
Corporate investment inherently relies on time horizon, as profits result from acquiring assets or developing capabilities that yield future benefits that exceed upfront costs. Despite the importance of time horizon to understanding resource allocation, knowledge about the subject has accumulated slowly. Our review therefore encompasses insights from several research streams that partially address the subject even though time horizon is not the central construct in any of them. We aim to clarify key constructs related to time horizon, organize prior research about the antecedents of time horizon, explain the implications of several theoretical traditions for time horizon, and detail the range of measures that have been used to capture time horizon empirically. By focusing narrowly on this topic but searching broadly for references, we provide integrative summaries of existing research and identify opportunities for new and unique research.
Keywords: behavioral strategy; decision making; dept.mgt; resource allocation/management

Mindfulness meditation and art appreciation as meaning-making practices - Yang, Charlie (Academy of Management, 2016)
Mindfulness has recently gained significant attention and momentum in academia and popular culture. There is, however, a paucity of literature on how students make sense of contemplative practices. This paper proposes that mindfulness meditation is not merely a useful tool for stress reduction, but also a metacognitive meaning-making practice.
Keywords: Art appreciations; Contemplative practice; Meaning makings; Metacognitives; Popular cultures; Stress reduction; dept.mgt

Gossip in organizations: from an evolutionary psychological perspective - Yang, Chulguen; Minjock, Robert; Voss, Bernard Edward; Colarelli, Stephen M (Academy of Management, 2014)
Gossip is often portrayed as a trivial and even destructive behavior at work. This paper integrates previous studies on gossip using a multilevel evolutionary framework and proposes a few empirical propositions to develop a more balanced view on gossip as a medium of informal communication in organizations.
Keywords: Evolutionary framework; Informal communication; dept.mgt

Language fluency as a factor in machine translation comprehension - Aiken, Milam; Park, Mina; Lindblom, Tobin (International Conference on Bioinformatics, 2013)
Keywords: dept.mgt

Pernicious performance appraisals: A critical exercise - Stepanovich, Paul L (Journal of Behavioral and Applied Management, 2013)
Keywords: dept.mgt

Telling tales at work: an evolutionary explanation - Yang, Chulguen (Business Communication Quarterly, 2013)
This article explores the adaptive functions of storytelling in the workplace from an evolutionary perspective. Based on the analysis of ethnographic studies on hunter-gatherer and modern work organizations, this article claims that storytelling, as an adapted cognitive device, was selectively retained by natural and sexual selection, because of its survival and reproductive payoff. The narrative production through storytelling is a natural coping mechanism and has been functional in both old and new ways of working life under different ecological conditions. This article also highlights underlying adapted psychological mechanisms of storytelling and discusses some evolutionarily informed practical implications and pedagogical applications. © 2013 by the Association for Business Communication.
Keywords: dept.mgt; narrative; oral presentations; organizational communication

Telling tales at work: an evolutionary psychological explanation - Yang, Chulguen (Academy of Management Proceedings, 2012)
Keywords: dept.mgt

Start-up and hiring practices of immigrant entrepreneurs: An empirical study from an evolutionary psychological perspective - Yang, Chulguen; Colarelli, Stephen M; Han, Kyunghee; Page, Robert A (International Business Review, 2011)
Strong social ties embedded in ethnic communities of immigrant populations have been considered key assets for immigrant entrepreneurs. However, little research has been done on how biological kinship and the biological theories of altruism influence the behavior of ethnic entrepreneurs. In this study, we have applied a neo-Darwinian evolutionary theory of kinship to examine adaptive functions of kin and ethnic altruism in business start-up and hiring practices of Korean immigrant entrepreneurs in the United States. We confirmed that the patterns of help received by Korean entrepreneurs for business start-ups were congruent with an evolutionary perspective on altruism. However, the results for hiring patterns suggested that customer ethnicity trumped kin and co-ethic interests. We close by offering suggestions for future research. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Ethnic nepotism; Evolutionary psychology; Immigrant entrepreneurship; Inclusive fitness theory; Kin altruism; dept.mgt

Biased against whom? The problems of “Group” definition and membership in test bias analyses - Colarelli, Stephen M; Han, Kyunghee; Yang, Chulguen (Industrial and Organizational Psychology, 2010)
Keywords: dept.mgt

Should employees be “dooced” for a social media post? The role of social media marketing governance - Parker, Janna M.; Marasi, Shelly; James, Kevin W.; Wall, Alison (Journal of Business Research, 2019)
Instances of employees being `dooced' because of a social media post are becoming commonplace. Three research questions are presented to better understand workplace firings due to social media posts using justice theory and social convergence to fit within the nomological net. The first question examines employees' awareness of their employer's social media policy. The second question examines the role of offensiveness in the perceived fairness of the termination. The third question asks whether work-related posts (social convergence) and the presence of a social media policy (social media governance) influence the perception of termination fairness. Two data collection efforts are presented to test the research questions. The research findings extend the social media marketing governance literature by incorporating role theory and script theory. Managerial implications include the importance of developing and communicating to employees the organization's social media policies.
Keywords: Justice theory; Role theory; Script theory; Social convergence; Social media marketing governance; Termination fairness; dept.mgt; peer-reviewed

Soft skill development in a total enterprise simulation - Frank, Ellen J (Business Education Innovation Journal, 2019)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Participant carelessness: Is it a substantial issue in survey research? - Marasi, S.; Wall, A.; Brewer, K. (Electronic Journal of Business Research Methods, 2019)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Automated translation preference with a bilingual chatbot - Park, Mina; Aiken, Milam (International Journal of Computers & Technology, 2019)
Free, online language translation services are being used by people around to the world to facilitate communication. However, it takes time and effort for a person to load the Web page in a browser, copy and paste text into the site, and translate words. The process quickly becomes tiresome. Instead, some computer programs are providing automated translation. However, no studies have been conducted to determine the efficiency or effectiveness of such an approach. In this study, we compare how students used an English-based chatbot with and without German automatic translation. Results show that students took nearly 1.5 times longer than their stated upper time limit to manually translate. In contrast, the automated translation was at least 30 times faster. In addition, the students were significantly more satisfied with the automated than the manual system.
Keywords: Chatbots; Google Translate; Tutor Mike; artificial conversation; dept.bis; dept.mgt; machine translation; peer-reviewed

Handbook on household hazardous waste - Cabaniss, Amy (Bernan, 2018)
Household hazardous waste (HHW) is a topic that affects every individual and community given the nearly universal use, storage, and disposal of chemical consumer products. Yet many communities lack the basic information, guidance, and planning support for HHW collection and management so that struggles (e.g., to gain politicians’ and residents’ support, host a collection, build a facility, affect behavior change, and encourage extended producer responsibility) continue on a regular basis. This book is for professionals, students, government officials and others interested in HHW and accommodating the increasing societal demand for this disposal option. In the evolving field of HHW collection and management, this book: provides an unparalleled, comprehensive look at household hazardous wasteis a must-have for anyone interested in the solid waste management field, whether novice or experienced, because of the valuable overview and specifics it provides for addressing the ubiquitous issue of HHWoffers perspectives based on many collective years of experts’ accrued insightthe chapters are written by leading practitioners and visionariesis packed with useful information on many aspects of HHW including its definition, mechanisms for collection and creative collection options, tools for behavior change, and product stewardshipoffers an extensive resource list for more information. Much has changed in 10 years since the first edition appeared, and each chapter in the Handbook on Household Hazardous Waste, Second Edition, is updated to reflect changes and advances in the field of HHW collection and management. This includes updated appendices and the extensive resource list.
Keywords: dept.mgt

Kinship ties and employee theft perceptions in family-owned businesses - O'Brien, Kimberly E; Minjock, Robert; Colarelli, Stephen M; Yang, Chulguen (European Management Journal, 2018)
Family business research typically views family firms using the frameworks developed for non-family businesses (e.g., agency theory, institutional theory). Thus, using an evolutionary perspective on family may help address gaps in the family business literature, particularly regarding deviance. In the current study, we use kin selection theory to predict that family members receive preferential treatment and this history of privileges can create entitlement and lead genetically-related employees to misuse company resources. Using an experimental vignette methodology and data from 161 people recruited from an online panel, we found that the participants' purported genetic relatedness to the owner of a business increased their theft intentions and decreased their expected severity of sanctions and likelihood of being reported. Biological sex moderated the relationships between genetic relatedness and theft intentions, as well as between expectations of punishment and theft intentions. Specifically, when females expected higher severity of sanctions or likelihood of whistleblowing, they were less likely to report theft intentions, compared to males. The results of this study suggest that family business owners should protect against theft by all employees, including genetic relatives. Future research using field samples would help provide context for these findings. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Counterproductive behaviors; Evolutionary theory; Family business; Kinship; Lab experiment; Nepotism; Theft; dept.mgt; peer-reviewed

Making sense of mindfulness in management education - Yang, Charlie (Developing a Sustainability Mindset in Management Education, 2018)
Keywords: dept.mgt

Pay openness movement: Is it merited? Does it influence more desirable employee outcomes than pay secrecy? - Marasi, Shelly; Wall, Alison; Bennett, Rebecca J. (Organization Management Journal, 2018)
Organizations are currently moving toward increased pay openness in the workplace; thus, it is important to determine the influence pay communication practices (pay secrecy and pay openness) have on employee outcomes and whether the increase in pay openness is merited and more beneficial for organizations. The purpose of this article is to analyze pay communication’s influence on workplace deviance and organizational citizenship behaviors (OCBs). Specifically, pay secrecy practices are hypothesized to influence employees to engage in less OCBs and more workplace deviance. Informational justice and distributive justice perceptions are included as mediators. Pay secrecy leads to greater workplace deviance as well as less OCBs and justice perceptions and thus, inferring the pay openness movement is merited. A Pay Communication scale was developed and validated for this study. Practical implications, limitations, and future research directions are provided. © 2018 Eastern Academy of Management.
Keywords: dept.mgt; distributive justice; informational justice; organizational citizenship behaviors; pay communication; pay openness; pay secrecy; peer-reviewed; workplace deviance

A Study on Cloud Computing Adoption Within Small and Mid-Size Businesses (smbs) - Richardson, Anthony; Mate, Geoffrey (International Journal of Interdisciplinary Research, 2018)
A growing number of organizations have difficulty scaling-up their IT infrastructure to handle their growing needs and increased resource demands. Digital Technology Platforms (DTPs) have been identified by Gartner, Inc. as one of the top 10 strategic technology trends of 2017. While DTPs may be mainstream and easily adopted by large enterprise-sized organizations, there is an opportunity for such platforms within Small and Mid-Size Businesses (SMBs). The bottom line is that computing and server hardware is expensive for SMBs. Furthermore, it may be difficult for SMBs to assess and price the labor and resources needed for a company to have acceptable performance while controlling costs. The purpose of this paper is to examine how cloud computing technologies are adopted by SMBs and the respective drivers associated with costs and capability that may reduce costs for an organization. This paper explores how four variables – Robust Capability, Limited Capability, Cost Constraint, and Resource Abundance interact to impact the adoption of DTPs within SMBs. Adopters of DTPs are classified as Efficient, Proactive, Resistive, and Reactive. With respect to adoption efficacy, a model is proposed for assessing the capability and resource readiness as correlated to SMB adoption of DTPs. A study of 12 SMBs and the implementations of DTPs is presented and posited with the proposed adoption model. Due to the extensive investments required in procuring infrastructure services –adoption enablement is imperative for SMB-sized organizations to realize a return on investment. Implications are discussed.
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Bullying in the workplace: The great balancing act of victim rights and organizational policies - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Journal of Competitiveness Studies, 2018)
Bullying in the workplace is considered a growing epidemic and organizations are struggling to ensure appropriate responses and protocol as there is currently no individual statutory remedy. This paper provides a synthesis of current research regarding workplace bullying, legal policies, efforts to promote remedial legislation and organizational responsibility and outcomes. Workplace bullying is addressed from several perspectives including organizational consequences, characteristics of both victims and perpetrators, the current state of legislation and best practices for organizational policy. The paper also provides a discussion of developing issues related to increased technology and social media usage.
Keywords: BULLYING in the workplace; CYBERBULLYING; VICTIMS of bullying; VIOLENCE in the workplace; WORK environment; dept.mgt; peer-reviewed; ⛔ No DOI found

Business schools, brand innovation and archetypal tradeoffs - Page Jr, Robert A.; Falk, Louis K. (Quarterly Review of Business Disciplines, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

How do humans interact with chatbots?: an analysis of transcripts - Park, Mina; Aiken, Milam; Salvador, Laura (International Journal of Management and Information Technology, 2018)
Keywords: dept.bis; dept.mgt; peer-reviewed

More than a decade later: Arational decision cycles in post-Hurricane Katrina disaster management - Smith Jr, Robert A.; Page Jr, Robert A.; Badr, Kauther S. (Quarterly Review of Business Disciplines, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Personality testing by employers: Balancing the need for qualified workers with individual rights - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition forum, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Corporate slavery: Does it still exist? - Wall, A.; Smith, R.; Nodoushani, O. (Competition Forum, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Teaching international business as an opportunity to develop cultural sensitivity - Frank, Ellen J. (Journal of Teaching in International Business, 2017)
Business program graduates are expected to perform with cultural sensitivity in international and intercultural professional environments. In order to support student development of the necessary mindset, a variety of assignments and activities have been integrated into the undergraduate International Business (IB) course. This article describes several types of exercises that can be used by anyone teaching this course or one where cultural sensitivity is an important component. No quantitative data are presented, nor are any claims made to the efficacy of these assignments. But student comments point to increased cultural sensitivity and a better understanding of the issues of globalization. © 2017 Taylor & Francis Group, LLC.
Keywords: Cross-cultural awareness; Cultural sensitivity; Globalization; International business (IB); dept.mgt

Classical literature gives life to business paradox and systems integration - Page, Robert; Andoh, Samuel; Smith, Robert (Administrative Issues Journal Education Practice and Research, 2017)
Keywords: dept.eco; dept.mgt

Workplace bullying: A growing epidemic - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Competition Forum, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Strategic corporate giving - Cha, Wonsuk; Park, Miyoung (International Journal of Corporate Strategy and Social Responsibility, 2017)
Keywords: dept.mgt

Leadership: A gateway to organizational innovation - Nodoushani, Omid; Stewart, Carol; Wall, Alison (Competition Forum, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Fair treatment of unauthorized restaurant workers as a sustainable competitive advantage - Page Jr, Robert A.; Smith Jr, Robert A.; Shrestha, Smita (Quarterly Review of Business Disciplines, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Entrepreneurship education: A look at two universities - Pauna, Diana; Frank, Ellen J. (Global Journal of Entrepreneurship, 2017)
Keywords: dept.mgt; ⛔ No DOI found

Insidious incentives: A critical exercise to explore knowing, context, and multiple views. - Stepanovich, Paul L; Hopkins, Pamela J; Stark, Ernest (Management Teaching Review, 2017)
Keywords: dept.mgt

Strategic conflict: A systems based pedagogical simulation - Stepanovich, Paul; Mueller, James (International Journal of Social Science and Education, 2017)
The paper describes a pedagogical simulation that allows students to explore strategic goal conflict within the context of systems theory. Systems theory emphasizes, among other things, complexity, non-linear relationships, unintended consequences, time delays, and dynamics. Another important aspect of systems thinking is contextual thinking, where objects or relationships cannot be taken as standalone or absolute, but are critically dependent on system structure and the environment. And while strategic planning has long emphasized the importance of environment, it may be difficult for students to experience or appreciate its importance in the planning process. The simulation provides an experiential exercise for a strategy course. The paper provides a summary of systems thinking and strategic goal conflict, a description of the simulation, teaching notes, and experience with the exercise.
Keywords: dept.mgt; ⛔ No DOI found